Sukorejo Community Harmonization in Religious Diversity in The Frame of Plural Society - Sahal Hanafi; M. Aryaduta Panatayudha; Eka Vasia Anggis (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The problem of intolerance that can lead to acts of radicalism is very dangerous for the unity of a nation. Intolerance has the potential to disappear if people in full awareness can accept a difference, the origin of differences can occur due to the influence of urbanization. Sukorejo Village is a concrete example of a plural society because of urbanization by outsiders with different backgrounds from one another. In this proceedings article using a qualitative research type method assisted by data collection techniques such as interviews/personal communication, observation, documentation. It was found that the social religious conditions in Sukorejo Village gradually eliminated the Paternalistic culture, then harmony in social interactions occurred even though each individual had a different religious background.